Bending of a porous piezoelectric cylinder under a thermal load. (February 2015) - Sladek, J.; Sladek, V.; Stanak, P.; Hrcek, S.
Abstract: A meshless method based on the local Petrov–Galerkin approach is proposed to analyze bending of a porous piezoelectric cylinder under thermal loading. Constitutive equations for porous piezoelectric materials possess a coupling between mechanical displacements and electric intensity vectors for solid and fluid phases. The influence of thermal expansion coefficients in solid and fluid phases on the plate deflection and on the induced electric potential is investigated via the local integral equation method developed in this paper. The spatial variation of displacements and electric potentials for both phases is approximated by the moving least-squares (MLS) scheme. The heat conduction equation is considered as uncoupled with respect to the mechanical and electrical fields.